HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN IBU HAMIL MENGHADAPI PROSES PERSALINAN DI KLINIK PRATAMATANJUNG KEC DELITUA KAB DELI SERDANG TAHUN 2019 - Megawati Sinambela; Reisy Tane (JURNAL KEBIDANAN KESTRA (JKK), 2020)
Family emotional support is an important factor for successful delivery time. A woman who has a harmonious relationship whith her husband will have fewer effects of emotional, physical symptoms, and complications during delivery time and adjust post-partum. Anxiety functions as a barometer to measure the level of social support. The purpose of this research is to know the relationship between the anxiety of pregnant women and the family support for delivery time at the Pratama Tanjung Clinic, Kec. Deli Tua, Kab. Deli Serdang. The method of this research is a servei analitik with cross sectional and technique for collecting sample is Aksidental sampling. The results test that showed there was a significant relationship between family support with the anxiety of pregnant women with P value = 0,020 (P < 0,05) of this research is using the chi-square conclusion the result showed that trere was a significant relationship between the anxiety of pregnant women and the family support for delivery time at pratama tanjung clinic suggestion pregnant women must always control her pregnance and expected to her families to accompany both at home and at the time for checking her pregnancy.